2015
DOI: 10.1007/s10853-015-9368-3
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-reinforced carbon composite foams with improved strength and EMI shielding from sucrose and graphene oxide

Abstract: Graphene-reinforced carbon composite foams were prepared by thermo-foaming of graphene oxide (GO) dispersions in molten sucrose to form solid organic foams followed by carbonization at 900°C. The hydrogen bonding interactions between sucrose hydroxyls and functional groups on GO decreased the melting point of sucrose from 185 to 120°C when the GO concentration increased from 0 to 1.25 wt%. The viscosity of GO dispersions in molten sucrose increased gradually with an increase in GO concentration up to 0.75 wt% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 73 publications
1
6
1
Order By: Relevance
“…(a) Proposed EMI shielding mechanism of FC-ANF/CNT aerogel films. (b) Comparison the EMI shielding performance of FC-ANF/CNT aerogel films with other shielding materials, including conducting polymers, metals, and nanoscale carbons at the X-band. ,, , (c) Plots of thickness-specific shielding effectiveness (SSE/t) versus density, where the SSE/t values of FC-ANF/CNT aerogel films are among the highest, compared to those of previously reported shielding materials. , …”
Section: Resultsmentioning
confidence: 99%
“…(a) Proposed EMI shielding mechanism of FC-ANF/CNT aerogel films. (b) Comparison the EMI shielding performance of FC-ANF/CNT aerogel films with other shielding materials, including conducting polymers, metals, and nanoscale carbons at the X-band. ,, , (c) Plots of thickness-specific shielding effectiveness (SSE/t) versus density, where the SSE/t values of FC-ANF/CNT aerogel films are among the highest, compared to those of previously reported shielding materials. , …”
Section: Resultsmentioning
confidence: 99%
“…67 GO (highly oxygenated graphene) was used instead of graphene since GO has good solubility in polar solvents in comparison to graphene. 68 Another work by DiMaio et al reported tetra ethyl ortho silicate (TEOS) as the molecular precursor solution to produce silica composites for nonlinear optic application with low CNT content (0.25 wt%). Although sol-gel reaction is ought to provide route to good dispersions, agglomeration in the precursor suspensions has been problematic.…”
Section: Sol-gel Processingmentioning
confidence: 99%
“…Narasimman et al studied the electrical conductivity in GO based carbon foams and found that higher wt% of GO (1.25%) showed an increase in electrical conductivity (4.8 S cm −1 ). [ 41 ] Figure 9 represents the conductivity network formed by RGO sheets in PF foam, which cause electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%